PENGARUH KESEJAHTERAAN KARYAWAN TERHADAP KOMITMEN ORGANISASIONAL YANG DIMODERASI OLEH WLOC (KONTROL KERJA) PADA CV. KEMBANG JAYA - Chandra, Yonathan Agung (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Welfare is required by employees within a company, that the welfare of the employees are fulfilled will motivate employees in a work, it will eventually affect the performance levels of the employee. Commitment to employees can be seen from the level of well-being of employees, the higher the level of well-being of employees getting high is also the employee's commitment to the company. WLOC (work locust of control) itself has the meaning or significance of a theory in personality psychology which refers to the extent to which individuals believe that individuals can control events that affect the individual. To that end, the study will provide a more in-depth study of the influence of organizational commitment on employee well-being and control work (WLOC) as moderator. In this study used is the conclusive research on the study of experimental or causal research. Sampling-taking techniques used are non probability sampling. The type of method used is the purposive sampling. The sample used was 150 employees of PT Kembang Jaya. Data were collected using a questionnaire. Analytical techniques used were linear regression analysis by using the SPSS program help moderators. The results of this analysis indicate that the welfare of the employees as positive and significant effect on organizational commitment in PT Kembang Jaya. It also found that the controls work (WLOC) as a moderator can strengthen the relationship between the welfare of employees with organizational commitment in PT Kembang Jaya.